2019
DOI: 10.1186/s12883-019-1295-5
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor imaging for assessment of microstructural changes associate with treatment outcome at one-year after radiofrequency Rhizotomy in trigeminal neuralgia

Abstract: Background Trigeminal neuralgia (TN) is characterized by facial pain that may be sudden, intense, and recurrent. Neurosurgical interventions, such as radiofrequency rhizotomy, can relieve TN pain, but their mechanisms and effects are unknown. The aim of the present study was to investigate the microstructural tissue changes of the trigeminal nerve (TGN) in patients with TN after they underwent radiofrequency rhizotomy. Methods Thirty-seven patients with TN were recruite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 35 publications
2
14
0
Order By: Relevance
“…DSI is a valuable tool for central nervous system imaging as it can be used to visualize the structural details of white matter bundles in multiple directions ( 14 , 28 30 ). Similar to previous studies ( 6 , 7 ), in our study, the FA value of trigeminal nerve on the affected side of TN patients was lower than that on the unaffected side and the decrease of FA value indicated that the integrity of white matter fiber bundle was damaged. However, in our study, AD, RD, and MD in the patient group did not increase significantly as previous studies.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…DSI is a valuable tool for central nervous system imaging as it can be used to visualize the structural details of white matter bundles in multiple directions ( 14 , 28 30 ). Similar to previous studies ( 6 , 7 ), in our study, the FA value of trigeminal nerve on the affected side of TN patients was lower than that on the unaffected side and the decrease of FA value indicated that the integrity of white matter fiber bundle was damaged. However, in our study, AD, RD, and MD in the patient group did not increase significantly as previous studies.…”
Section: Discussionsupporting
confidence: 90%
“…As a non-invasive magnetic resonance imaging (MRI) technique to evaluate the integrity of white matter, diffusion tensor imaging (DTI) can indirectly reflect the integrity of nerve fiber bundles by measuring the diffusion movement of water molecules ( 5 ), thus providing new insights into the etiology of TN. Previous studies ( 6 , 7 ) have shown that in patients with TN, DTI parameters such as fractional anisotropy (FA) decreased significantly and axial diffusivity (AD), radial diffusivity (RD), and mean diffusivity (MD) increased significantly. However, some studies ( 8 , 9 ) argued different or even opposite opinions of the changes of DTI metrics values between affected and unaffected sides in patients and controls.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting partial volume effect with adjacent CSF will reduce FA and elevate MD erroneously. For example, MD values in the unaffected CNV of TN patients have ranged from 1.2‐4.3 x 10 −3 mm 2 /s, 4,5,7,11,14–17 which is 1.5‐5–fold greater than that expected of adult white matter (~0.8 x 10 −3 mm 2 /s). However, the effects of partial volume and CSF contamination may be reduced by improving spatial resolution.…”
Section: Introductionmentioning
confidence: 87%
“…Many previous nerve DTI studies of CNV in TN have employed low resolution “whole‐brain” acquisition protocols with thick slices of 2 mm or greater, yielding large voxel volumes of 2 x 2 x 2 = 8 mm 3 5,7,14 or 1.9 x 1.9 x 3 = 10.8 mm 3 4,6,15,16 relative to a comparatively small structure. The resulting partial volume effect with adjacent CSF will reduce FA and elevate MD erroneously.…”
Section: Introductionmentioning
confidence: 99%
“…[16] Also recent study reported that increased trigeminal nerves volume and FA, and a decreased ADC, AD, and RD represent the pathophysiology of TN, and decreased trigeminal nerves volume, FA, and AD compared with the normal side after a one-year follow-up of partial rhizotomy (PR) of sensory root of trigeminal nerve. [3] These studies provided us information and concepts that DTI and its diffusivity metrics may have clinical signi cance for microstructural change and prognosis evaluation.…”
Section: Introductionmentioning
confidence: 99%